Pneumonia acquired in the Community - María Caridad Fragoso Marchante; Iris González Morales; Dianelis Sierra Martínez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
A bibliographical revision of the main aspects in the diagnosis and treatment of the patients suffering from pneumonia acquired in the community is carried out. Microorganisms responsible for this type of pneumonia are mention in this paper as well as the available diagnostic methods for germs isolation. Different guidelines for diagnosis and treatment of this disease published by several medical societies and scientific institutions are analyzed by means of a review of the stratification index of the patients used in each of them. Aspects related to the duration of the treatment and the possible causes associated with the unfavorable evolution are stated.